Mechanical and Biodegradation Behaviour of Jute/ Polylactic Acid Green Composites - Preet Singh, Jai Inder; Singh, Sehijpal; Dhawan, Vikas (Asian Journal of Engineering and Applied Technology, 2018)
Global warming, diminution of fossil fuels, escalating oil price’s are the major reasons which forces the researchers to develop green products for the sustainable development. In this research work, green composites have been developed with jute fibers as reinforcement and poly lactic acid as matrix material using compression moulding technique. All composites were developed with maintaining the reinforcement as 30% fiber volume fraction. The influence of curing temperature with the range of 160°C, 170°C and 180°C was investigated for various mechanical properties of developed composites and degradation behaviour of developed composites were analysed using soil burial test. Results acquired from the tests specify that the tensile and flexural strength decreases with upsurge in curing temperature. Morphology study using scanning electron microscopy is further justified the findings obtained from mechanical tests. Biodegradation study was done on the all the three different composites under the soil burial conditions for 9 months and results indicate that composites developed at 160°C degrade faster as compared to others. This study also gives an optimum curing temperature for the development of jute/PLA composites.